Penyuluhan Seks Bebas Di Yayasan Wasangkerta Dusun Karangdawa Kecamatan Setu Patok Cirebon Jawa Barat - Rachmawati, Diana Widhi; Mulyana, Yusep; PN, Trinandari; Zuliyana, Meti; Agustina, Juaidah; Permatasari, Nuryanti (Journal of Smart Community Service, 2023)
Free sex is a complex social issue that affects various aspects of people's lives. Free sex behavior can have a significant negative impact on social development and health. The Wasangkerta Foundation in Karangdawa Hamlet, Cirebon, realizes the important role of education in overcoming the problem of free sex among teenagers and society. Counseling with the title "Free Sex Counseling" aims to increase awareness of the dangers of free sex and encourage responsible behavior in society. The Wasangkerta Foundation is a partner in this service, showing a commitment to overcoming social issues such as free sex. An educational and participatory approach is used to create awareness about the negative effects of free sex and how to prevent them. This service method uses interactive and participatory counseling methods, involving various elements of society from various age groups. The aim is to ensure that messages about the importance of maintaining sexual health and preventing promiscuous sex are well received and implemented in daily life. This service hopes to make a positive contribution to increasing public awareness and knowledge about free sex as well as encouraging changes in responsible behavior in sexual relations. It is also hoped that the continuation of this counseling will create a society that is aware of the importance of healthy and responsible behavior in sexual relations.